Usefulness of early post‐operative liver function test monitoring after laparoscopic common bile duct exploration. Issue 11 (14th July 2015) - Wewelwala, Chandika; Cashin, Paul; Berry, Roger; Blamey, Stephen; Jones, Gregory E.; Croagh, Daniel G.
Abstract: Background: This study examines the usefulness of early post‐operative liver function test (LFT) monitoring in predicting retained choledocholithiasis after laparoscopic common bile duct exploration (LCBDE). Methods: Data on patients who had LCBDE over a 3‐year period were collected retrospectively. Patients who had ongoing choledocholithiasis after unsuccessful LCBDE were considered for the test group and patients who had successful LCBDE were considered for the control group. Preoperative, day 1 post‐operative and day 2 post‐operative alkaline phosphatase (ALP), gamma glutamyl transferase (GGT), alanine transaminase (ALT) and bilirubin levels were recorded. Proportions of patients who had worsening LFTs were analysed in each group. Results: Proportions of patient who had worsening LFTs on day 1 were not statistically different between two groups and they were statistically equal on equivalence testing (two one‐sided tests). On day 2, proportions of patient were again not statistically different. Bilirubin and ALT were statistically equivalent ( P = 0.022 and P = 0.025 respectively) but GGT and ALP failed to achieve statistical equivalence ( P = 0.062 and P = 0.138 respectively) on day 2. Twelve patients with normal appearing final intraoperative cholangiogram needed reintervention due to retained choledocholithiasis diagnosed subsequently. LFTs progressively improved despite presence of choledocholithiasis in eight of these 12 patients (75%) and only four were diagnosed by worsening post‐operative LFTs during index admission. Conclusion: LFTs in the early post‐operative period are not useful in determining which patients require biliary imaging or intervention after an apparently successful LCBDE.